2022
DOI: 10.1155/2022/4206857
|View full text |Cite
|
Sign up to set email alerts
|

The Application of RBF Neural Network Model Based on Deep Learning for Flower Pattern Design in Art Teaching

Abstract: The rapid growth of artificial intelligence technology has been deployed in art teaching and learning. Radial basis function (RBF) networks have a completely different design compared to most neural network architectures. Most neural networks consist of multiple layers that can introduce nonlinearity by repetitive application of nonlinear activation functions. In this research, people will study the application of the RBF neural network model based on deep learning in flower pattern design in art teaching. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…Everyone may examine the exhibits at the e-museum and interact with them at their own speed, which encourages greater openness to learning. It is a great strategy for involving, educating, and entertaining students, as well as giving older and more seasoned art aficionados fresh information, viewpoints, and freedom (Bello & Mohamed, 2018;Xiao & Luo, 2022).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Everyone may examine the exhibits at the e-museum and interact with them at their own speed, which encourages greater openness to learning. It is a great strategy for involving, educating, and entertaining students, as well as giving older and more seasoned art aficionados fresh information, viewpoints, and freedom (Bello & Mohamed, 2018;Xiao & Luo, 2022).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…It estimates positive result count while evaluating system of art education. Then the formula is derived in equation (17).…”
Section: ) Precisionmentioning
confidence: 99%
“…The investigation outcomes of DL demonising auto encoders were enhanced through the application of machine learning algorithms, which also provided references for data processing, stability, security of digital art education platforms [16]. Lastly, even though industrial hazardous gas tracking process suggested by has some relevance to topic of art education platform, findings of the parallel optimization framework, energy usage reduction research provide particular references for platform's optimization, on-going development [17]. The research mentioned above, which covered techniques and technologies from numerous industries, produced significant improvements and optimizations for this platform [18].…”
Section: Introductionmentioning
confidence: 99%
“…Input the number of items into the classroom teaching quality evaluation system, evaluate the student scoring situation, and analyze the quality of art teaching courses (Cheng et al, 2018). For the expected results, this article evaluated curriculum (Xiao & Luo, 2022). This article selects ten courses based on the ratings of various supervising experts and distributes a questionnaire survey to students.…”
Section: Analysis Of Neural Network Evaluation Modelmentioning
confidence: 99%